2012
DOI: 10.1111/j.1464-410x.2012.11078.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cognition and sensation in determining when and where to void: the concept of cognitive voiding

Abstract: Study Type – Aetiology (case series) Level of Evidence 4 What's known on the subject? and What does the study add? The factors taken into consideration when determining when and where to void are poorly understood. Studies on bladder sensations, obtained during cystometry of from voiding diaries, are proving difficult to transfer to everyday experiences. There is therefore a need to explore what does influence when and where to void. This study, using focus groups, highlights the fact that many voids are drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…This afferent outflow does not appear to be part of the autonomic reflexes involved in the control of the coordination of micturition (Barrington’s reflexes). For reasons that will be argued below, it is possible that this system is a reasonable candidate to contribute to the sensations of “awareness” as the bladder fills 4 , 6 . It is also a candidate for modulation.…”
Section: “Afferent Noise” and The Concept Of The Peripheral Regulatiomentioning
confidence: 99%
See 1 more Smart Citation
“…This afferent outflow does not appear to be part of the autonomic reflexes involved in the control of the coordination of micturition (Barrington’s reflexes). For reasons that will be argued below, it is possible that this system is a reasonable candidate to contribute to the sensations of “awareness” as the bladder fills 4 , 6 . It is also a candidate for modulation.…”
Section: “Afferent Noise” and The Concept Of The Peripheral Regulatiomentioning
confidence: 99%
“…These sensations alone do not trigger a reflex void. Rather the information appears to be used in a complex decision making process 4 . The sensation of bladder “awareness” during filling has been shown to increase progressively as the bladder is filled at a constant rate 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Urinary continence results from a complex mechanism which involves PFM contraction but also cognitive integration. Harvey et al developed the concept of cognitive voiding. They showed that urinary continence is under the influence of many key factors including conscious (temporal map, voiding behavior, habituation…) and unconscious orders (bladder filling, urinary continence sympathetic reflex…).…”
Section: Discussionmentioning
confidence: 99%
“…Participants in the current study were requested to rate their average sensation over a month. In daily life, it is likely that people choose to void for a variety of reasons, with different bladder volumes and levels of sensation . It is possible that if “tingling” is associated with a full bladder, it may be rarely experienced in a day‐to‐day context.…”
Section: Discussionmentioning
confidence: 99%